(untitled) (Wallingford, 2010)
Tropical coastal deltas represent one of the most diverse and rapidly changing biophysical regions in the developing world. These deltas are home to large populated areas, are significant centres of agricultural production and industrial development, and contain fragile ecosystems that are now facing new threats as a result of expected sea-level rises associated with global warming. Focusing on the developing countries of Asia, Africa and South America, chapters explore the diverse livelihoods of people in these areas and the impact of land-water management on the environment. New techniques and methodologies are explored in land and water management to try and solve the conflicts between rice-based agriculture, aquaculture, fisheries and the environment in tropical delta regions. Illustrating how to protect tropical deltaic systems in the face of serious future challenges, this will be essential reading for students, researchers, policy makers and natural resource managers in agriculture and aquaculture
Keywords: Sử dụng nước,Nghề cá,Thủy sản,Aquaculture,Fisheries,Water use; Quản lý,Nhiệt đới,Nhiệt đới,Tropics,Tropics,Management; Các nước đang phát triển,Developing countries